2019
DOI: 10.1097/mjt.0000000000000773
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing HIV Pre-exposure Prophylaxis Practices via an Educational Intervention

Abstract: Brief, focused training on HIV prevention promotes awareness, acceptance, and likelihood of prescribing PrEP by internal medicine trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…Similar findings were reported in a survey of internal medicine residents (N = 48), of whom 22% were unaware of PrEP and 62% had fair or poor awareness of side effects. PrEP was considered effective or safe by only 78% or 66% of participants, respectively [98].…”
Section: Side Effects/medication Interaction Concerns As a Barrier Tomentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings were reported in a survey of internal medicine residents (N = 48), of whom 22% were unaware of PrEP and 62% had fair or poor awareness of side effects. PrEP was considered effective or safe by only 78% or 66% of participants, respectively [98].…”
Section: Side Effects/medication Interaction Concerns As a Barrier Tomentioning
confidence: 99%
“…Counseling on the benefits of PrEP, and providing information and reassurance on the risk and monitoring of short-and long-term side effects, may also improve adherence to PrEP [119]. It is also imperative that educational interventions are targeted to primary care providers, including training to increase PrEP knowledge [120] and to alleviate concerns regarding PrEP safety [98]. Concerns around risk compensation (or an increase in risk-taking behaviors among individuals at risk prompted by a decrease in perceived HIV risk) appear to be one factor that can cause reluctance among some healthcare providers to prescribe PrEP to eligible patients [53].…”
Section: Potential Solutions To Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the central role of lay HIV workers in PrEP implementation, it is critical to understand their implementation behaviors related to PrEP. Unlike previous evaluation of PrEP trainings that primarily focused on investigating whether the trainings had any effects on trainees' knowledge [15,18,20], confidence of [18][19][20] and comfort level in discussing PrEP with clients [16], we systematically assessed determinants of implementation behavior through a valid and reliable questionnaire (DIBQ) [47,48]. We observed a positive influence of the training on almost all DIBQ domains, suggesting the training's potential in mobilizing and motivating lay HIV workers to participate in upcoming PrEP implementation in China.…”
Section: Discussionmentioning
confidence: 99%
“…Training lay HIV workers is therefore a critical implementation strategy for PrEP [14]; evaluating such trainings is necessary to generate evidence on effective and efficient approaches to build capacity of lay HIV workers to support PrEP implementation. Previous published studies of PrEP capacity building efforts have reported on training of internal medicine residents [15,16], primary care providers [17], family planning providers [18], and the whole HIV care team [19,20]. To our knowledge, there is no published data on approaches to and evaluation of trainings that specifically target lay HIV workers to facilitate PrEP implementation.…”
mentioning
confidence: 99%